Safety and feasibility of laparoscopic radical resection for bismuth types III and IV hilar cholangiocarcinoma: a single-center experience from China - Wang, Jianjun; Xia, Yang; Cao, Yuan; Zeng, Xintao; Luo, Hua; Cai, Xianfu; Shi, Mingsong; Luo, Huiwen; Wang, Decai (Frontiers in Oncology, 2023)
Background: Surgery represents the only cure for hilar cholangiocarcinoma (HC). However, laparoscopic radical resection remains technically challenging owing to the complex anatomy and reconstruction required during surgery. Therefore, reports on laparoscopic surgery (LS) for HC, 2 especially for types III and IV, are limited. This study aimed to evaluate the safety and feasibility of laparoscopic radical surgery for Bismuth types III and IV HC.The data of 16 patients who underwent LS and 9 who underwent open surgery (OS) for